Stop LaRouche banner - Sahl, Ted (photographer):::Creator::::::::::::
BAYMEC (Bay Area Municipal Elections Committee) activists hold a "Stop LaRouche" banner in celebration of the defeat of Proposition 64. Included in this group are Arthur Morris III, David Treadwell, Wiggsy Sivertsen, Don Nelson and Ken Yeager.